“Efecto de la aplicación de bioestimulantes foliares, sobre el rendimiento del cultivo de arroz (Oryza sativa L.), sembrado en secano.” - Martínez Jiménez, Freddy Fernando (2018)
VIII. SUMMARY The present experimental work was carried out in the lands of the "Los Mangos" farm, located at Km. 4 of the Vía Jujan - Simón Bolívar. This objective was to know the effect of the application of foliar biostimulants on the yield of rainfed rice cultivation. The INIAP FL 14-80 Cristalino rice variety was planted in plots 15m2, two biostimulants were evaluated: Franquer supra (free amino acids) and Sagastim (folic acid, Cysteine), with and without mixtures at different doses, distributed in ten treatments and three repetitions using the experimental design complete blocks randomly. The evaluation and comparison of means were made with the Tukey test at 5% significance. At the end of the crop cycle, plant height, number of tillers per m2, panicle number per m2, length of panicles, number of grains per panicle, days to flowering, leaf analysis, days to harvest, weight of thousand grains, were evaluated. Yield per hectare and economic analysis. The results determined that the applications of Flanquer Supra 0.8 L / ha + Sagastim 0.4 L / ha (6697.60 kg / ha) increased the yield of grain with increases of 60% with respect to the control treatment. Likewise, the applications of biostimulants intervened directly in the variables, plant height, number of tillers, number of panicles, number of grains per panicles, yield per hectare. Keywords: biostimulants, foliar, yield, rice